Analisis Krisis Penginjilan Di Kalangan Gereja Di Indonesia - Georges Nicolas Djone (Kamaya: Jurnal Ilmu Agama, 2022)
Evangelizing which is commonly called "preaching the good news" is not only a belief that has been bestowed on every person who believes in Jesus Christ, but also an obligation that His church must carry out as one of the priority tasks. However, evangelism in fact ranks as the fourth leading cause of the growth in the number of congregations in the church in the last ten years with a figure of only 1.7%. This study aims to analyze the causes of the crisis of evangelism among churches in Indonesia in an effort to maximize the implementation of the fulfillment of the Great Commission of Jesus Christ. The descriptive qualitative approach is the method used in the implementation of this research by analyzing and collecting data through book sources and digital articles, as well as journals and other documents related to the topic that is the subject of the study. As a result, the causes of the crisis of evangelism among churches in Indonesia are due to: First, some believers feel they are not called to be evangelists and so feel unable to evangelize. Second, some believers know that preaching the Good News is the responsibility of believers and the church, but are afraid of the threats that can be experienced related to carrying out the preaching of the gospel. In conclusion, evangelism is not an option that can be chosen, but the obligation of every believer based on love for God and neighbor. The crisis in the implementation of evangelism has proven to be hampering the growth of the church in Indonesia, because without the implementation of evangelism, it is difficult to see the Kingdom of God being enlarged on this earth.